Lorentzian Para‐Kenmotsu Manifolds Within the Framework of ∗‐Conformal η ‐Ricci Soliton - Kishor, Shyam; Bhardwaj, Arun Kumar; Mani, Naveen; Shukla, Rahul (Journal of applied mathematics, 2025)
The present article intends to study the ∗‐conformal η ‐Ricci soliton on n ‐LPK ( n ‐dimensional Lorentzian para‐Kenmotsu) manifolds with curvature constraints. On n ‐LPK, we derive certain results of ∗‐conformal η ‐Ricci soliton satisfying the Codazzi‐type equation, R ( ξ , L ) · S = 0, the projective flatness of the n ‐LPK manifold. At last, we conclude with an n ‐LPK manifold with conformal η ‐Ricci solitons using a suitable example.